2004
DOI: 10.1136/bmj.328.7451.1293
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of human papillomavirus testing in women with borderline or mildly dyskaryotic cervical smear test results: cross sectional questionnaire study

Abstract: Objective To describe the psychological impact on women of being tested for human papillomavirus (HPV) when smear test results are borderline or mildly dyskaryotic. Design Cross sectional questionnaire study. Setting Two centres participating in an English pilot study of HPV testing in women with borderline or mildly dyskaryotic smear test results. Participants Women receiving borderline or mildly dyskaryotic smear test results tested for HPV and found to be HPV positive (n = 536) or HPV negative (n = 331); an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
172
2
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 26 publications
12
172
2
7
Order By: Relevance
“…The kind of information that is provided about HPV is likely to affect the impact of testing positive for the virus, although we have identified specific information that appears to be reassuring. Perhaps most important, and consistent with the findings of Maissi et al (2004), is the need for clear and consistent information about HPV to minimise the anxiety associated with uncertainty and confusion. This need is illustrated very clearly by the following quote:…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The kind of information that is provided about HPV is likely to affect the impact of testing positive for the virus, although we have identified specific information that appears to be reassuring. Perhaps most important, and consistent with the findings of Maissi et al (2004), is the need for clear and consistent information about HPV to minimise the anxiety associated with uncertainty and confusion. This need is illustrated very clearly by the following quote:…”
Section: Discussionmentioning
confidence: 78%
“…This is the first study to use qualitative methods to gain an indepth understanding of the perceptions of women taking part in HPV testing in the context of cervical cancer screening, rather than questioning women hypothetically (McCaffery et al, 2003;Anhang et al, 2004) or using quantitative methods to measure anxiety (Maissi et al, 2004;McCaffery et al, 2004a). It is considerably strengthened by the inclusion of women from contrasting ethnic and socioeconomic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside clinical and economic considerations, it has been argued that psychosocial issues also need to be taken into account when deciding whether and how to introduce HPV testing [3,4]. A few studies have indicated that testing positive for HPV may impose a significant psychological burden on the women taking part in screening, over and above the impact of an abnormal smear result [5][6][7]. This seems to be due, at least in part, to the fact that as a sexually transmitted infection (STI), HPV carries connotations of stigma and raises issues for relationships that are not commonly experienced when receiving an abnormal smear result.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly we investigated whether women experience long-term anxiety and distress about being HPV positive while waiting for their second test. On-going anxiety has been found in some women with mildly abnormal cytology who are managed by surveillance [8][9][10] and it is possible that this could be more severe among women who are HPV positive, as the psychosocial burden of testing positive for HPV seems to be greater than the impact of an abnormal smear result [5][6][7]. There is currently no effective means of treating HPV, so women may face on-going positive status without resolution.…”
Section: Introductionmentioning
confidence: 99%
“…HPV infections can lead to cancers and precancers of the cervix (2), anus, penis, vagina and vulva (3,4), anogenital warts (5,6), and recurrent respiratory papillomatosis (7,8), with growing evidence for a role in the pathogenesis of cancers of the head and neck (9). A diagnosis of HPV can lead to distress (10), shame, and anger and negatively affect sexual activity and enjoyment (11).…”
Section: Introductionmentioning
confidence: 99%